Financial Markets and Online Advertising Demand: Reevaluating the Dotcom Investment Bubble - Crain, Matthew (AoIR Selected Papers of Internet Research, 2013)
This paper outlines the connections between the dotcom investment bubble and the growth of online advertising. In the latter half of the 1990s, speculative investors funded the lavish advertising expenditures of a host of largely unprofitable dotcom companies through which billions of dollars poured into the online advertising sector. This generated a surge of demand for online ad services and helped to legitimize the internet as an advertising channel. These outlays were rationalized through a New Economy ideology that greatly privileged marketing practices. Advertising became the cornerstone of dotcom business strategy, essential to not only win customers, but also to attract further investment. While the period is often dismissed as a false start in the history of the web’s commercial development, it is better conceived of as highly generative of modern structures of online advertising.